2004
DOI: 10.3748/wjg.v10.i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on lipid metabolism and musculoskeletal fitness in female athletes

Abstract: AIM:This study investigated the effects of intense training on lipid metabolism, bone metabolism and bone mineral density (BMD) in female athletes. METHODS:Sixty-six female subjects participated in this study, age ranging from 18 to 55 years. The sample group included thirty-six athletic subjects and the control group comprised thirty non-athletic individuals. Five athletes competed with national level (5/36) and nine non-athletic subjects (9/30) were postmenopausal women. The assessment items included body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Mechanical loading in athletes and associated bone modeling and remodeling should be associated with increased levels of bone turnover markers, and hypoestrogenism in athletes with amenorrhea could cause a further increase in bone resorption markers. Higher levels of osteocalcin, a bone formation marker, have been reported in adolescent compared to adult athletes [36], consistent with the increased state of bone turnover in the adolescent years, and one study in adult athletes did report an increase in urinary deoxypyridinoline (a bone resorption marker) with intense training [49]. Conversely, in our study of adolescent athletes, we observed lower levels of both a bone formation marker (PICP) and a bone resorption marker (N-telopeptide) in adolescent athletes with amenorrhea compared with sedentary controls, whereas levels in eumenorrheic athletes were somewhere in between [23].…”
Section: Bone Turnover In Adolescent Athletesmentioning
confidence: 73%
“…Mechanical loading in athletes and associated bone modeling and remodeling should be associated with increased levels of bone turnover markers, and hypoestrogenism in athletes with amenorrhea could cause a further increase in bone resorption markers. Higher levels of osteocalcin, a bone formation marker, have been reported in adolescent compared to adult athletes [36], consistent with the increased state of bone turnover in the adolescent years, and one study in adult athletes did report an increase in urinary deoxypyridinoline (a bone resorption marker) with intense training [49]. Conversely, in our study of adolescent athletes, we observed lower levels of both a bone formation marker (PICP) and a bone resorption marker (N-telopeptide) in adolescent athletes with amenorrhea compared with sedentary controls, whereas levels in eumenorrheic athletes were somewhere in between [23].…”
Section: Bone Turnover In Adolescent Athletesmentioning
confidence: 73%
“…There were limited data on the relationship between VJ and BMI, and thus its correlation with other MF indexes. Only a few studies described the VJ performance in certain populations, such as athletes or sports players [32, 33]. As a predictor of bone health, higher VJ may indicate a better status of bone mineral density [34].…”
Section: Discussionmentioning
confidence: 99%
“…In order to revert this situation, the adoption of methods aimed at the increase of the slim mass with the consequent increase on the metabolic conditioning and the lipids mobilization, especially in fat tissue, liver, heart, skeletal muscles and in the plasma lipoproteins (7) , becomes necessary. One of the methods that may lead to this objective is the physical activity (8) . The effect of different training situations -static (vertical staircase) and dynamic (treadmill) -on the long extensor muscles of fingers and soleus muscles in young rats was studied by Melichna et al (9) .…”
Section: Introductionmentioning
confidence: 99%